Preventing Knowledge Loss in Gojek by Assessing the Company’s Readiness to Implement Knowledge Management - Saptono, Savitha; Hendarman, Achmad Fajar (Jurnal Studi Manajemen dan Bisnis, 2023)
The objective of this research would be to understand the readiness level of Gojek in introducing knowledge management in the company , understand the strength and areas of improvement for Gojek’s knowledge management, and discover the tools that can be used to implement knowledge management in Gojek. The main method used to get primary data is through the quantitative method and is collected via questionnaire, while the qualitative data used  to further enrich the main data collected is through forum group discussions. The results showed that Gojek is still at the expansion phase, where the efforts of knowledge management is present in several business units and the company see’s the benefits of knowledge sharing.  Gojek could further develop itself by using people as its accelerator and become champions of knowledge. Having a committed people team would further create a knowledge sharing culture that could be followed by the whole pod of the company. In order for the employee to have a single source of knowledge, it is important to create a knowledge management tool which can be done by leveraging the existing portal that Gojek already has for employees: OneGojek. What needs to be added is the ability to store employee knowledge in order to make information accessible for all employees.